The Analysis of Green Environment Movement Campaign in Supporting National Food Security of Indonesia (Global Journal of Human-Social Science, 2018)
This study aims to analyze and describe the implementation process of green environmental movement campaign in supporting national food security through hydroponic farming campaign conducted by Military District Command (KODIM) 0503 West Jakarta. The concepts used are the public relations, public relations campaigns, and environmental communication. The method used in this research is qualitative research with single case study design. This research revealed that the green environment movement campaign, in supporting national food security through cultivation activity with hydroponics technique, covers three stages:1) Problem identification, which is to review and identify the problem prior to campaign program implementation, 2) Campaign management, which is to identify the characteristics of target audiences in order to formulate messages, campaign actors, campaign channels, and technical campaign implementation, 3) Evaluation stage, which is to see how many people have started this green environmental movement campaign program at their home.. The results of this study suggested the following: 1) to add more varied campaign media, 2) a brand ambassador for the campaign program, 3) to strengthen media relations activities for campaign publicity purposes, 4) to add quantitative methods in conducting surveys on the success of the campaign program.
Keywords: campaign; environment; hydroponics